SUFI RITUAL PRACTICES AND PERCEIVED MENTAL WELL-BEING: INSIGHTS FROM INDONESIA’S COVID-19 PANDEMIC EXPERIENCE (Lembaga Pengembangan Kinerja Dosen, 2022)
The COVID-19 pandemic has not only caused a global health emergency but has also generated profound psychological challenges, particularly in the form of fear, anxiety, and uncertainty about mortality. In Indonesia, where religious and spiritual traditions play a central role in daily life, Sufi orders (ṭarīqa) have provided unique coping mechanisms that integrate spiritual discipline with collective resilience. This study specifically investigates how members of the Qadiriyya-Naqshbandiyya (TQN) order in Indonesia engaged in Sufi ritual practices to preserve mental well-being during the pandemic. Using a qualitative design, data were collected through in-depth interviews, participant observation, and textual analysis of Maklumat (directives) issued by the spiritual leader Abah Aos. Thematic analysis revealed three major dimensions of coping: intrapersonal regulation through dhikr and contemplative practices; communal reinforcement through manāqib gatherings, synchronized rituals, and charitable acts; and existential reframing of mortality within a Sufi theological worldview. Findings indicate that these ritual-based strategies successfully reduced stress and anxiety, strengthened emotional resilience, and reinforced social cohesion during lockdowns. Participants also reported perceived physical health benefits, which may be explained through psychoneuroimmunology pathways linking stress reduction to immune resilience. Importantly, the study highlights that Sufi coping operates not only as an individual psychological resource but also as a culturally embedded resilience system. The implications extend beyond the religious domain, offering valuable lessons for public health by integrating spiritual and cultural resources into mental health interventions. This research contributes to interdisciplinary discussions on religion, resilience, and well-being, underscoring the relevance of indigenous spiritual traditions in addressing global crises such as COVID-19.